FOMER CHILD SOLDIERS: PRODUCT OF ARMED CONFLICTS AND HOW THE INTERNATIONAL CRIMINAL COURT FAILS TO SEE ITS SIGNIFICANCE - Dino Panji Pananjung; Sigar Aji Poerana (Padjadjaran Journal of International Law, 2019)
AbstractIn armed conflicts, children are often kidnapped and forced to become child soldiers, they are also given forced indoctrination (by violence and threats) and are taught to commit crimes, such as looting and murder. Disobeyed children and those who try to escape will be punished in the form of torture or even being executed in front of other children's soldiers as a lesson so others will not follow their step. When they did not serve the armed forces anymore or they grew up and no longer held child status, they were given the title of "former child soldiers". These former child soldiers might still live in rebellious environments and commit serious crimes including international crimes under jurisdiction of International Criminal Court when they grow up. This research argues whether the International Criminal Court considers the historical status of the perpetrators who are former child soldiers as mitigating factor of their punishment. The research method used is the juridical normative approach. The result of this research shows the International Criminal Court has never considered the history of international criminals as child soldiers. However, the International Criminal Court may use the consideration beside what has been regulated in Rome Statute, such as Article 21(3). This is also based on the Judge's right for discretion in the Rome Statute to adjudicate, as what we can see in the Case of Omar Khadr. Keywords: Child Soldier, Criminal responsibility, International Criminal Court, Judgment and Sentencing, Rome Statute. AbstrakDalam konflik bersenjata, anak seringkali diculik dan dipaksa menjadi tantara anak, mereka juga didoktrin paksa (melalui kekerasan atau ancaman) serta diajakan untuk melakukan kejahatan seperti menjarah dan membunuh. Mereka yang tidak menurut dan yang mencoba melarikan diri akan dihukum dengan disiksa di hadapan para tantara anak lainnya sebagai contoh agar tidak ditiru oleh anak lainnya. Mereka disebut “mantan tantara anak” setelah tidak lagi menjadi teantara atau telah dewasa. Tidak menutup kemungkinan ketika dewasa mereka hidup dengan jiwa pemberontak dan melakukan kejahatan serius bahkan kejahatan internasional yang menjadi jurisdiksi Mahkamah Pidana Internasional. Penelitian ini membahas apakah Mahkamah Pidana Internasional mempertimbangkan riwayat seorang pelaku kejahatan internasional yang menjadi seorang mantan tentara anak untuk meringankan hukuman mereka. Metode penelitian yang digunakan adalah yuridis normatif. Hasil penelitian menunjukkan bahwa praktik Mahkamah Pidana Internasional tidak pernah mempertimbangkan latar belakang pelaku kejahatan internasional sebagai mantan tentara anak. Namun, Hakim Mahkamah Pidana Internasional dapat menggunakan ketentuan diluar Statuta Roma berdasarkan pasal 21(3). Hal ini juga didasari pada adanya diskresi Hakim untuk memutus dan mengadili diluar yang diatur di dalam Statuta Roma, seperti halnya Kasus Omar Khadr. Kata Kunci: Mahkamah Pidana Internasional, Pemidanaan, Pertanggungjawaban Pidana, Statuta Roma, Tentara Anak.